Tingkat Ketaatan Pengobatan Pada Penderita Gangguan Psikotik Fase Awal Di Yogyakarta - RACHMAN, Achmad Aulia ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Psychotic disturbance is a mental disturbance which the patient loss contact with reality. Approximately 5,8% Indonesian suffer from this disturbance. Antipsychotic medication may cause many side effects. Side effect is one of the predictor for non adherence in antipsychotic medication. Non adherence is a common thing among patients with psychotic disturbance. There is a direct relationship between non adherence and relapse rate, but there is no clear relation between side effect and medication adherence. Objective : To identify the relationship between side effect and medication adherence on patient with first episode psychosis in Yogyakarta. Method : Cross-sectional, the data was taken between the period of October 2010 and March 2011. A number of 100 test subjects from RSUP Dr. Sardjito, RSJ Gharasia, RSK Puri Nirmala, RSUD Wates, RSUD Bantul and RSUD Gunung Kidul were gathered. Caregivers were given “medication adherence” form to be filled wether the patient took medication or not. Result : 2 of 100 sample had experienced side effect of neuroleptic drug. Most of the sample showed non adherence to medication (40%). The statistical results is p-value=0,022 and CC=0,267 Conclusion : There is a relationship between side effect and medication adherence on patient with firstepisode psychosis with a weak correlation’s degree